2020
DOI: 10.1002/cbic.202000511
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Bioactivity of Iridium(III) Phenanthroline Complexes with Halide Ions and Pyridine Leaving Groups

Abstract: A series of half‐sandwich structural iridium(III) phenanthroline (Phen) complexes with halide ions (Cl−, Br−, I−) and pyridine leaving groups ([(η5‐CpX)Ir(Phen)Z](PF6)n, Cpx: electron‐rich cyclopentadienyl group, Z: leaving group) have been prepared. Target complexes, especially the Cpxbiph (biphenyl‐substituted cyclopentadienyl)‐based one, showed favourable anticancer activity against human lung cancer (A549) cells; the best one (Ir8) was almost five times that of cisplatin under the same conditions. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…M-OH 2 aqua complexes are often more reactive than the corresponding complexes. 37 The hydrolysis characteristics of IrMPOH, RuMPOH, IrPOH and RuPOH were measured by UV-vis absorption spectroscopy (Fig. 5 and Table 2), and the presence of DMSO ensured the solubility of these complexes.…”
Section: Hydrolysis Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…M-OH 2 aqua complexes are often more reactive than the corresponding complexes. 37 The hydrolysis characteristics of IrMPOH, RuMPOH, IrPOH and RuPOH were measured by UV-vis absorption spectroscopy (Fig. 5 and Table 2), and the presence of DMSO ensured the solubility of these complexes.…”
Section: Hydrolysis Studiesmentioning
confidence: 99%
“…These results can lead to the accumulation of intracellular reactive oxygen species (ROS, 1 O 2 ) and lead to cell death. [37][38][39] One rational approach to improve the efficacy of metal complexes consists of incorporating different chelating ligands with complementary biological activity to enhance the physiological targets of the metallodrug. 40 In this context, P-donor ligands represent an unquestioned tool in bioinorganic medicinal chemistry for improving the anticancer activity of metal complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was confirmed that 1-4 were stable in water (D 2 O with the addition of MeOD for solubility) for a period of 48 h. This is important information because rapid hydrolysis of halido (X) half-sandwich [M(η 6 /η 5 -arene/yl)(L)(X)] + complex cations to their aqua species [M(η 6 /η 5 -arene/yl)(L)(H 2 O)] 2+ can result in strong binding to biomolecules, which may lead to deactivation and decrease in their cytotoxicity. 33,71 Analogically, after the addition of PBS buffer (in a MeOD/ D 2 O solution mixture) solution stability was also observed, but in this case only for 1-3. Interestingly, complex 4 underwent partial I − to Cl − ligand exchange, due to the presence of an excess of the chloride anions originating from PBS in solution.…”
Section: Biological Studiesmentioning
confidence: 80%
“…While these results are in striking contrast to analogue N,C – complexes recently reported by our group that present IC 50 values well within the submicromolar range, the IC 50 results reported here corroborate our hypothesis that using a stable tether ring system renders the iridium complex biologically inactive and allows the use of such systems as prodrugs for controlled metallodrug activation. Complexes of the general formula [Ir­(η 5 -Cp*R­(N,N)­Z] n + , where N,N is en, bipy, or phen and Z = halido or pyridine, which could represent the nontether versions of our half-sandwich tethered iridium­(III) complexes, have, in fact, been reported to present moderate activity, ranging from a few micromolar (similar to that of cisplatin) to >100 μM, in cell lines such us A2780 and A549 using similar cell viability protocols. Dinuclear half-sandwich iridium­(III) complexes, bearing extended π systems as chelating and bridging N,N ligands, have also been reported that exert cytotoxicity similar to that of cisplatin in a number of cell lines …”
Section: Results and Discussionmentioning
confidence: 99%